2018
DOI: 10.1111/jfd.12935
|View full text |Cite
|
Sign up to set email alerts
|

Capsular polysaccharide of Streptococcus agalactiae is an essential virulence factor for infection in Nile tilapia (Oreochromis niloticus Linn.)

Abstract: Streptococcus agalactiae (Group B Streptococcus, GBS) is associated with diverse diseases in aquatic animals. The capsule polysaccharide (CPS) encoded by the cps gene cluster is the major virulence factor of S. agalactiae; however, limited information is available regarding the pathogenic role of the CPS of serotype Ia piscine GBS strains in fish. Here, a non‐encapsulated mutant (Δcps) was constructed by insertional mutagenesis of the cps gene cluster. Mutant pathogenicity was evaluated in vitro based on the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 37 publications
(58 reference statements)
0
12
0
Order By: Relevance
“…Based on our research on S. agalactiae characterization, we could isolate 2 major serotypes, serotype Ia and serotype III, that caused disease in tilapia, which was similar to the surveillance in other countries in SE Asia such as Malaysia [ 17 , 21 , 22 , 37 , 38 , 39 ]. Based on our findings, both serotypes showed similar distribution throughout Thailand during 2012–2014; however, it was found that serotype III exhibited higher virulence than serotype Ia [ 21 ].…”
Section: Discussionmentioning
confidence: 55%
“…Based on our research on S. agalactiae characterization, we could isolate 2 major serotypes, serotype Ia and serotype III, that caused disease in tilapia, which was similar to the surveillance in other countries in SE Asia such as Malaysia [ 17 , 21 , 22 , 37 , 38 , 39 ]. Based on our findings, both serotypes showed similar distribution throughout Thailand during 2012–2014; however, it was found that serotype III exhibited higher virulence than serotype Ia [ 21 ].…”
Section: Discussionmentioning
confidence: 55%
“…Although many reports stress the importance of CPS in the survival of GBS in hosts (Hammerschmidt et al, 2005; Lowe et al, 2007; Millard et al, 2012; Zeng et al, 2016; Zhang et al, 2019), studies on GBS Sia are limited. In the present study, we successfully constructed the ΔSia mutant by neuA‐D gene cluster deletion from GBS WC1535 by homologous recombination method to explore the role of GBS Sia in host–pathogen interaction and evaluate the potential of the ΔSia mutant as a live attenuated vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…A previously established approach was used to observe the WT and ΔSia mutant WC1535 using transmission electron microscopy (TEM) (Zhang et al, 2019). Bacteria in the logarithmic growth phase were collected and fixed in phosphate buffer containing 2.5% glutaraldehyde.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, using tilapia challenge assays, CPS-deficient GBS showed attenuated pathogenesis. And this mutant GBS was also cleared more easily from tilapia spleen tissue compared to the wild type GBS strain examined [ 34 ]. It is now understood that CPS can suppress the aggregation of the complement factor C3b to inhibit phagocytotic killing by host cells [ 35 , 36 ].…”
Section: Virulence Factorsmentioning
confidence: 99%